A world without princes [Svet bez princov anglicky] / [book 2] - Chainani, Soman (The School for Good and Evil, 2014)
Witches and princesses reside at the School for Girls, where they've been inspired to live a life without princes, while Tedros and the boys are camping in Evil's old towers. A war is brewing between the schools, but can Agatha and Sophie restore the peace?